The social impact of HIV/AIDS in India. (April 2016) - Solomon, S; Kumarasamy, N; Challacombe, SJ
Abstract : This paper is based on the last public lecture given by Dr Solomon at the 7th World Workshop on Oral Health & Disease in HIV/AIDS, held in Hyderabad, India, in November 2014. It examines the social impact of HIV in India and the founding of the Y.R. Gaitonde Center for AIDS Research and Education (YRG CARE) clinic in Chennai, India, by Dr Suniti Solomon and her colleagues. This is a story of prejudice and ignorance throughout the various social levels in India. Reports of India's first AIDS case surfaced in 1986, when female sex workers were found to be HIV positive. The first voluntary counseling and testing center, part of a sexually transmitted diseases (STD) clinic, was set up to increase awareness about the epidemic. To address the rapid spread of HIV infection in Tamil Nadu and the existing stigma in society and hospitals, Dr Solomon established YRG CARE in 1993. She recognized that fear and panic about HIV led to widespread social prejudice against HIV‐positive patients, even within hospitals. By the end of 2014, over 34 000 patients had accessed these services and 20 000 HIV+ patients had been registered, nearly 40% of whom were females. The team embarked on a statewide awareness program on HIV and sexuality, covering over two hundred schools and colleges educating them about prevention strategies and combating the social stigma attached. The grass‐root work of YRG CARE in the management of HIV infections revealed a widespread prejudice, due largely to the lack of awareness about the subject. It is estimated that even in 2015, as little as 40% of HIV‐infected people are formally diagnosed and have access to care. In a country as socially and culturally diverse as India, there is much more to be carried out to build on the pioneering work of Dr Solomon.